EFEKTIVITAS PEMBERIAN TERAPI RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI : LITERATURE REVIEW - Ismail, Ismail; Basri, Muhammad; Sukriyadi; Kordja, Baharuddin; Rahmatia, Sitti (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Background:Hypertension is a health problem that is still penetrating in various parts of the world, even more widespread along with the times. The disease is characterized by an increase in blood pressure reaching 140/90 mmHg or more. One way to reduce high blood pressure is to use non-pharmacological treatment methods, one of which is progressive muscle relaxation therapy. This approach focuses attention on the muscles by identifying tense ones and then reducing those tensions to achieve a sense of relaxation. Thus, blood pressure and heart rate can decrease significantly Objective: to assess how effective progressive muscle relaxation therapy is in reducing blood pressure in individuals suffering from hypertension with a literature study approach. Method: This research utilizes the literature study method using secondary data sources, namely articles obtained from three trusted databases, namely Google Scholar, Researchgate, and Onesearch. The criteria used as a reference for selecting articles to be reviewed include publication time in the last 5-10 years, using Indonesian or English, being original, available in full text form, and indexed. From the selection process, a total of 10 articles were considered worthy of review, consisting of five articles in Indonesian and five articles in English. This research focused on a comprehensive literature review of both languages to gain an in-depth understanding of the research topic. Thus, it is expected that this research can make a significant contribution to the understanding and development of science and technology in a broader context. By using a literature study approach and a rigorous selection process for the articles reviewed, it is hoped that this research can provide a comprehensive and accurate understanding of the issues discussed in this study. Results: In ten articles that have been compiled, it is explained that the use of progressive muscle relaxation therapy has the potential to reduce systolic and diastolic blood pressure in individuals suffering from hypertension. Conclusion: progressive muscle relaxation therapy is effective in reducing blood pressure in hypertensive patients, based on the arguments outlined earlier.